Genetic engineering and its impact on life sciences: A review - Konkala Anand (AG Volumes, 2025)
Genetic engineering has emerged as a transformative field within life sciences, enabling precise modification of genetic material for applications in agriculture, medicine, industry, and environmental management. This review presents an overview of key genetic engineering tools and techniques, including recombinant DNA technology and CRISPR-Cas systems, and examines their roles in drug development, gene therapy, crop improvement, and industrial biotechnology. In addition, ethical, ecological, and safety concerns associated with genetically modified organisms are discussed, highlighting the need for balanced regulation and responsible use of these rapidly advancing technologies.